(untitled) (Research, Society and Development, 2020)
It aims to report the experience of students and professors of the nursing college in carrying out educational actions with users of the Family Health Strategy (FHS), in the municipality of Divinópolis - MG through academic extension. This is an experience report about the actions developed by the academic extension project entitled ´´Education in health: prevention of breast cancer in the municipality of Divinópolis / MG``, from June to December 2017. The theater was presented five times, being attended by more than 800 people, at the FHS and at the State University of Minas Gerais UEMG - Divinópolis unit. During the performance of the theater, it was explained clearly in a simple and easy to understand language about what breast cancer was about. The use of active methodologies in academic education and used by health professionals corroborates a critical and reflective view, going beyond technical and fragmented forms.